From orexin receptor agonist YNT-185 to novel antagonists with drug-like properties for the treatment of insomnia - Mezeiova, Eva; Janockova, Jana; Konecny, Jan; Kobrlova, Tereza; Benkova, Marketa; Dolezal, Rafael; Prchal, Lukas; Karasova-Zdarova, Jana; Soukup, Ondrej; Korabecny, Jan (Bioorganic chemistry, 2020)
YNT-185 is the first known small molecule acting as orexin 2 receptor (OX2R) agonist with implication to narcolepsy treatment, served as a template scaffold in generating a small set of seven compounds with predictive affinity to OX2R. The design of the new small molecules was driven mostly by improving physicochemical properties of the parent drug YNT-185 in parallel with in silico studies, later suggesting their favorable binding modes within the active site of OX2R. We obtained seven new potential OX2R binders that were evaluated in vitro for their CNS availability, cytotoxicity, and behavior pattern on OX2R. Out of them, 15 emerged as the most potent modulator of OX2R, which, contrary to YNT-185, displayed inverse mode of action, i.e. antagonist profile. 15 was also submitted to an in vivo experiment revealing its ability to permeate through BBB into the brain with a short half-life.
Keywords: YNT-185; Aniline Compounds; aniliny; Molecular Structure; Insomnia; Orexin Receptors; molekulární struktura; lidé; Benzamides; Orexin 2 receptor antagonist; Sleep disorder; Suvorexant; benzamidy; orexinové receptory; poruchy iniciace a udržování spánku; Sleep Initiation and Maintenance Disorders; Humans